2015
DOI: 10.2514/1.i010343
|View full text |Cite
|
Sign up to set email alerts
|

Student Choice and Persistence in Aerospace Engineering

Abstract: This longitudinal multi-institution study examines student outcomes and demographics in aerospace engineering in the United States over the period of 1987 to 2010. This large sample allows adoption of an intersectional framework to study race/ethnicity and gender together. In this paper, the demographics of students who choose aerospace engineering, their six-year graduation rates, trajectories of students entering and leaving aerospace engineering, and the "stickiness" of the discipline are examined. Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…Although more recent data are available in MIDFIELD, the most recent data used in this study are from 2011. The specific dataset used in this study was frozen in 2011 to permit a series of single‐discipline studies (Brawner et al, ; Brawner, Lord, et al, ; Lord et al, ; Lord, Layton, & Ohland, ; Lord, Ohland, & Layton, ; Ohland et al, ; Orr, Lord, Layton, & Ohland, ; Orr, Ramirez, Lord, Layton, & Ohland, ; Pilotte et al, ). Thus, using a consistent dataset makes it possible to consider those studies in relation to this multidisciplinary exploration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more recent data are available in MIDFIELD, the most recent data used in this study are from 2011. The specific dataset used in this study was frozen in 2011 to permit a series of single‐discipline studies (Brawner et al, ; Brawner, Lord, et al, ; Lord et al, ; Lord, Layton, & Ohland, ; Lord, Ohland, & Layton, ; Ohland et al, ; Orr, Lord, Layton, & Ohland, ; Orr, Ramirez, Lord, Layton, & Ohland, ; Pilotte et al, ). Thus, using a consistent dataset makes it possible to consider those studies in relation to this multidisciplinary exploration.…”
Section: Methodsmentioning
confidence: 99%
“…While the complete MIDFIELD dataset is large and growing, frequently only a subset of it is used for a particular study. The data for this study were the same dataset used in a large number of other published studies that included only students ever enrolled in engineering and only data elements that have one value per student (Brawner et al, ; Brawner, Lord, et al, 2015; Lord et al, ; Lord, Layton, & Ohland, ; Lord, Ohland, & Layton, ; Orr et al, ; Orr et al, ; Ohland et al, ; Pilotte et al, ). That is, term‐by‐term data such as term GPA, courses taken, and other fields were omitted.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies that have investigated engineering major choice have done so at the postsecondary level (e.g., Griffith & Main, 2019; Lord et al, 2019; Main et al, 2018; Main, Xu, et al, 2017). Other studies focused on engineering major choice and persistence have used data from the Multiple‐Institution Database for Investigating Engineering Longitudinal Data (2020); for example, see Lord et al (2019), Main et al (2015), Orr et al (2014, 2015), and Pilotte et al (2017). Orr et al (2015), for example, focused on major choice and persistence in aerospace engineering by gender and race/ethnicity, and reported that Black men and women as well as Asian women have particularly low persistence rates in engineering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This work has helped to change the conversation in engineering education, by demonstrating that the appearance of a particularly high rate of attrition is actually the result of a higher-than-typical retention rate, but a replacement rate that is much lower than other disciplines [2]. MIDFIELD results have shown that women are as likely as men to persist in engineering, that women follow similar pathways to men if they leave engineering, [3] and that student demographics and outcomes vary by engineering discipline, gender, and race [4,5,6,7,8,9,10,11]. Research with MIDFIELD has also shown that the way persistence is measured can result in a "systematic majority measurement bias" [12] and revealed that students who migrate into engineering disciplines are successful [13].…”
Section: Background On Midfieldmentioning
confidence: 99%